Using bibliometric analysis techniques to understand the recent progress in school travel research, 2001–2021. (December 2021) - Jing, Peng; Pan, Kewen; Yuan, Daibiao; Jiang, Chengxi; Wang, Wei; Chen, Yuexia; Shi, Yuji; Xie, Junping
Abstract: Background: Mode choice of school travel has significantly changed over the past decades. The rate of active school travel (cycling and walking from/to school) has been declining worldwide, causing a series of urban problems. Methods: We reviewed 343 publications (2001–2021) from Web of Science and PubMed using bibliometric analysis. Specifically, a first step described the field of school travel using descriptive statistical analysis. A second step applied network analysis to identify existing research clusters and future research directions. Results: In this systematic review, the current academic situation was analyzed, such as the most productive areas, journals, and institutions in the field of school travel. The USA is the most productive country with five institutions among the top 15. Journal of Transport & Health is the journal with the highest number of published articles. The co-occurrence network of articles was divided into three clusters: effect factors of active school travel, policy and public transportation, and school bus. A keyword analysis identified vital research topics, methods, and fields. Conclusions: There has been a significant increase in research interest in the field of school travel. Institutions from the USA play a vital role in studies of school travel. Exploring the effect factors of active school travel is the hot topic of the domain. Exploring the influence that automated driving that brings will be the domain frontier in this field. It is observed that the field of school travel will be of enormous growth with the multi-subject and multimethod and more academic cooperation. Highlights: A systematic overview of existing literature from 2001 to 2021 is presented in the field of school travel. This is the first study on school travel with the method of bibliometric and content analysis. Exploring the effect factors of active school travel is the hot topic of the domain.